2014
DOI: 10.1097/igc.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HE4 in Ovarian Cancer Follow-up: A Review

Abstract: These preliminary data start to suggest a superiority of HE4 over CA-125 in the detection of ovarian cancer recurrence. Moreover, the prognostic role of HE4 could help clinicians to personalize the follow-up program, whereas its predictive role could be useful to plan the treatment of the relapse. The role of HE4 in ovarian cancer follow-up deserves to be further investigated in prospective randomized multicentric studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…HE4 is expressed in the Mullerian type epithelium of ovarian cortical inclusion cysts which suggested that HE4 might be a significant predictor for Mullerian-derived tumors [13]. A prominent upregulation of HE4 immune expression has been seen in female genital cancers, especially in ovarian serous and endometrioid carcinomas.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…HE4 is expressed in the Mullerian type epithelium of ovarian cortical inclusion cysts which suggested that HE4 might be a significant predictor for Mullerian-derived tumors [13]. A prominent upregulation of HE4 immune expression has been seen in female genital cancers, especially in ovarian serous and endometrioid carcinomas.…”
Section: Discussionmentioning
confidence: 96%
“…A prominent upregulation of HE4 immune expression has been seen in female genital cancers, especially in ovarian serous and endometrioid carcinomas. Detection of HE4 expression with immunohistochemical staining in several studies has revealed that HE4 is expressed in all endometrioid adenocarcinomas, 90% of serous adenocarcinomas and 50% of clear cell epithelial ovarian cancers [12,13]. Interestingly, high HE4 tissue expression is mostly found in epithelial ovarian adenocarcinomas [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as being useful for diagnosing pelvic masses, testing for serum HE4 levels is beginning to acquire an important role as a potential biomarker for monitoring treatment and detecting relapse [33] (Table 4).…”
Section: He4mentioning
confidence: 99%
“…Pre-clinical elevation of CA125 is seen several months prior to clinical recurrence [41]. A review by Piovano et al (2014) looking at HE4 currently has no recommendation regarding its incorporation into clinical practice [42] although elevated levels may be more sensitive at detecting relapse then serum CA125 [43]. The use of other tumour markers such as CEA and routine imaging have not been recommended for asymptomatic women from a Cochrane review of ovarian cancer follow-up [44].…”
Section: Follow-up In Gynaecological Oncologymentioning
confidence: 99%